DIGITAL DISRUPTIVE INNOVATION: PARADOX or CONCEPTUAL DISTORTION? - Rodrigues, Leonel Cezar; Riscarolli, Valeria; Jesus, Marco Antônio Sampaio de; Zucco, Fabricia Durieux (Revista de Negócios, 2018)
Cultures that incorporate new knowledge produced elsewhere in the industrial or academic environment need rethink the basic elements of knowledge they incorporate, or else they may incur huge conceptual distortions or even superficial absorption, without intrinsic value. This seems to be the case of concept on disruptive innovation.Â Itâ€™s conceptual purposes seem to be distorted as disruptive innovation spreads through academia and industry. The main objective of this research is to identify the conceptual premises of disruptive innovation in selected cases of digital disruptive innovation, to characterize an epistemology meaning to it. The methodology is quantitative. We used the CAPES journal base and Publish or Perish, evaluating the articles and performing a textual scan with the Iramuteq software. The main results indicated that there are two clusters of concepts of disruptive innovation, one from the context of established companies and another from the context of new companies, originated as result of digital transformations. Conclusions lead to same conceptual logic in both concepts. However, conceptual logic based on events of established companies, is epistemologically more dogmatic than the one that considers disruptive innovation in the context of digital companies, which is more typically perspectivist.